EFEKTIVITAS PEMBELAJARAN BERBASIS DARING PADA MASA PANDEMI COVID 19 MENGGUNAKAN MEDIA ONLINE DI SMAN 22 MAKASSAR - Irma Suryani Suryani; Abdul Muis; Dian Perdana Hasba3; Marnia Marnia (Universitas Cokroaminoto Palopo, 2022)
This study aims to identify online learning activities where students can access learning as an effort to support government programs, namely study from home during the Covid 19 pandemic and student responses to learning media used during online learning. The research method in this research is descriptive quantitative research. The population of this study were students of class XI MIPA in SMA Biringkanayya District, Makassar City, namely SMAN 22 Makassar, SMAN 18 Makassar and SMAN 15 Makassar as many as 595 students. The sample in this study were students of class XI MIPA 3 each in SMA Biringkanayya District, Makassar City. The research instrument in this study is a questionnaire in the form of a Google form. Research data obtained by distributing questionnaires in the form of Google forms, and interviews. Based on the results of the study, that online media learning has four indicators, namely understanding the material online, learning time, being able to focus attention, and enthusiasm in participating in effective lessons during the Covid 19 pandemic in Biology subjects at SMA Biringkanayya District, Makassar City. The most effective online learning media used during online learning during the Covid 19 pandemic in Biology subjects at Biringkanayya High School Makassar City are SMAN 22 Makassar using Google Classroom, SMAN 18 Makassar Zoom Meeting and SMAN 15 Makassar Google Classroom.